Kajian Ketahanan Pangan Rumah tangga Pedesaan Dalam Upaya Peningkatan Status Gizi Masyarakat di Kabupaten Lampung Selatan - Anggun Rusyantia; Dwi Haryono; Eka Kasymir (Jurnal Penelitian Pertanian Terapan, 2010)
The objective of this study to analyze the dominant factors that potentially could affect the food security of households in the village of Trimomukti, Candipuro District and the village of Kelawi, Bakauheni District, South Lampung Regency; look for the dominant factors that potentially could affect the nutritional status of children and how the relationship between household food security levels with nutritional status of children in the region. Results showed the average household energy adequacy in both villages is still highly dependent on food energy contribution of cereals, especially rice. Based on logistic regression model, Greater the number of members in a household with low income and food expenditure against revenue high, and obtained a principal food source rice from membeli or aid and subsidies as well as from the community Kelawi Village will have greater opportunities for prisoners vulnerable to lack of food.Based on ordinal logistic regression model, increasing age of a toddler with food consumption of energy sources that do not meet the need and the ratio of food expenditure of households on incomes greater, the chances these children will experience moderate malnutrition will be higher and even worse. Seen the relationship between household food security with nutrition status, if a food is resistant to household, the nutritional status of children under five will get better. Regional differences in factors that contribute to the adequacy of the village of rice per capita did not have a significant influence on household level food security and nutritional status of children. Keywords: food security, household, nutrition status